PENENTUAN HARI PERNIKAHAN MENGGUNAKAN PRIMBON DARI SISI ISTIHSAN - Syamsuri Syamsuri; Ilham Effendy (Fakultas Agama Islam Universitas Nurul Jadid, 2021)
The determination of the wedding day by using primbon happened in Karanggeger’s society is a Tradition that has been inherited by the ancestors, as in Islam this tradition certainly contradicts with Islamic Shari'a, where as the majority of the Karanggeger people are Muslim, but the tradition is still carried out as a habit that has been handed down for generations by the society, to determine the law from that tradition by using Istihsan, where Istihsan assesses an event based on whether or not there are benefits in it.How to find out the process of determining the marriage contract day in Karanggeger village by using Primbon and how the Istihsan study of the determination of marriage contract by using the primbon. This research used some methods those are Phenomenology, Observation, Interview, and Documentation. The data obtained is then processed with a qualitative approach.The results of the study were that Karanggeger people came to the local religious figures who understood the Primbon problem then determine a good wedding day, every thing that was done and considered something good was worthy of being called Istihsan, as well as legal exclusion from general shari'ah principles, based on habits applicable.